Economic systems and risk preferences: evidence from East and West Germany - Michael Neugart (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
For standard economic models it is typically assumed that preferences are given and stable. But do economic systems shape individuals' risk preferences? Using the reunification of East and West Germany as a natural experiment I evaluate differences in financial risk taking comparing Eastern and Western German households for almost two decades after the fall of the Berlin Wall. Controlling for a large set of socio-economic variables East Germans having been ``treated'' by a command economy were more prone to taking financial risk than West German citizens. The differences were quantitatively relevant after the fall of the Iron Curtain and almost vanished by 2008.
Keywords: D14; G11; P50; 330